PARTO CESÁREO E ÍNDICE DE MASSA CORPORAL EM CRIANÇAS ENTRE 1 A 3 ANOS DE IDADE: análise do efeito causal - CAVALCANTE, Lilian Fernanda Pereira (2017)
Introduction: Obesity rates are rising significantly in the world. Cesarean delivery has been associated with increased obesity at all stages of life. Our objective was to evaluate the causal effect between cesarean delivery and body mass index in children. Methods: A cohort study was carried out, including 3,205 children between 1 and 3 years of age, born in 2010. After birth, 5,475 mothers and children were evaluated. Information on the type of delivery, maternal and child characteristics such as sociodemographic, morbidity and anthropometric conditions were collected. For the analysis of the causal effect a Directed Acyclic Graphs (DAG) was constructed to select the variables for minimum adjustment. Statistical analysis showed interchangeability between groups. Overweight in children by body mass index for age was defined by z> +2 score. Results: Of the 3,205 children evaluated (51.3% female), 48% were born by cesarean delivery, only 0.2% of the newborns were small for gestational age and 8.9% of the children were overweight. There was inadequacy of prenatal care in 37.8% of pregnancies. There is no causal relationship between cesarean delivery and body mass index in children between 1 and 3 years of age. Conclusion: The causal effect of cesarean section on the BMI of children was not observed. Through the methodology used, it was possible to attenuate possible biases of confounding and collision, and interchangeability between groups was observed.